Ex ante economic assessment of impacts of GM maize and cassava on producers and consumers in Tanzania - Ruhinduka, Remidius D.; Falck-Zepeda, José B.; Wood-Sichra, Ulrike; Zambrano, Patricia; Semboja, Haji; Chambers, Judith A.; Hanson, Hillary; Lesseri, Gerald (International Food Policy Research Institute, 2020)
Despite agriculture’s key role in Tanzania, agricultural productivity has remained relatively low compared with that of most other countries producing similar crops globally. Recent innovations in the sector such as development of genetically modified (GM) crop varieties with traits targeted to specific contextual challenges could revolutionize the country’s agricultural performance. Tanzania is attempting to deploy drought- and pest-resistant (WEMA) maize as well as brown-streak-disease-resistant cassava varieties. But little is known, contextually, about potential economic impacts of these crop varieties on Tanzanian farmers and consumers. This study implements an ex ante impact assessment to answer such important policy questions. Using DREAM, a model that estimates economic surplus as projections of consumer and producer gains from the use of a technology, complemented with locally collected and validated data, we document positive net economic impacts from the potential adoption and use of both maize and cassava GM varieties. Results are robust to various sensitivity tests and methodological cross checks that consider a range of values for production markets, performance, and adoption assumptions. Adoption of a GM crop is predicated on compliance with regulatory and other governance requirements, proper product dissemination and stewardship, and the technology’s effectiveness in addressing producer productivity issues. Special attention needs to be paid to reducing regulatory and governance delays so as to minimize inefficiencies and potential coordination issues that may arise over time.